Cultural differences in acceptability of a vaginal microbicide: a comparison between potential users from Nashville, Tennessee, USA, and Kafue and Mumbwa, Zambia - Montgomery Rice V (Dove Medical Press, 2012)
Valerie Montgomery Rice,1 Margaret C Maimbolwa,2 Esther Munalula Nkandu,2 Jacqueline Fleming Hampton,3,* Jae-Eun Lee,4 James EK Hildreth51Morehouse School of Medicine, Atlanta, GA, USA; 2School of Medicine, University of Zambia, Lusaka, Zambia; 3Meharry Medical College, Center for AIDS Health Disparities Research, Nashville, TN, USA; 4RCMI Translational Research Network Data and Technology Coordinating Center, Jackson State University, Jackson, MS, USA; 5Dean, College of Biological Sciences, University of California Davis, Davis, CA, USANote: at the time the research was conducted, Dr Montgomery Rice was the Executive Director, Center for Women's Health Research, Meharry Medical College, Nashville, TN, USA, and Dr Hildreth was the Director, Center for AIDS Health Disparities Research, Meharry Medical College, Nashville, TN*Dr Fleming Hampton has passed away since this manuscript was written. We wish to honor her memory by including her as an authorPurpose: We sought to determine the relationship between acceptability of a hypothetical vaginal microbicide, cultural factors, and perceived HIV risk among African-American women in Nashville, TN, USA, and African women in Kafue and Mumbwa, Zambia.Patients and methods: Women in both sites completed a survey. Regression analyses were performed on valid samples (Nashville, 164; Zambia, 101) to determine cultural differences affecting microbicide acceptability. Regression analyses also tested whether individual risk perception affected acceptability.Results: In Zambia, 89.6% of women were willing to use a microbicide versus 81.6% in Nashville (P < 0.0001). One cultural difference is that women in the Zambian cohort viewed risk of HIV infection as distinct from risk of acquiring STIs, with 48% believing they were certain to become infected with AIDS, compared to 4% of Nashville participants.Conclusion: These results suggest a high degree of acceptability toward use of a vaginal microbicide to prevent HIV infection.Keywords: HIV/AIDS, women, birth control, sexually transmitted infections